2019
DOI: 10.1002/biof.1585
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin ameliorate complete Freund's adjuvant induced rheumatoid arthritis via targeting NF‐κB/MAPK signaling pathway

Abstract: Rheumatoid arthritis (RA) is a chronic and accelerated autoimmune illness with proliferative and damaging synovitis, resulting in joint death and cartilage and bone erosion. This study focused on the potential therapeutic effect of wogonin on complete Freund's adjuvant (CFA) induced RA in rats and the underlying mechanisms. Arthritis was experimentally caused in rats by subcutaneously injecting 0.1 mL of CFA into the subplantar area of the left hind paw under moderate anesthesia on day zero. The regular oral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…For example, wogonin played protective role against myocardial infarction by repressing oxidative stress through the activation of Nrf2/HO‐1 pathway 49 . Besides, wogonin was capable of ameliorating the severity of rheumatoid arthritis and nephrotoxicity resulted from cadmium and cisplatin by lessening oxidative stress 13,14,50 . Consistent with these reports, our findings further confirmed the potent anti‐oxidative capacity of wogonin in treating septic liver injury via the activation of Nrf2.…”
Section: Discussionsupporting
confidence: 87%
“…For example, wogonin played protective role against myocardial infarction by repressing oxidative stress through the activation of Nrf2/HO‐1 pathway 49 . Besides, wogonin was capable of ameliorating the severity of rheumatoid arthritis and nephrotoxicity resulted from cadmium and cisplatin by lessening oxidative stress 13,14,50 . Consistent with these reports, our findings further confirmed the potent anti‐oxidative capacity of wogonin in treating septic liver injury via the activation of Nrf2.…”
Section: Discussionsupporting
confidence: 87%
“…Concurrent treatment of dexamethasone challenged rats with wogonin at either 30 mg/kg or 60 mg/kg doses improved the antioxidant defenses SOD, CAT, and GSH and alleviated dexamethasone-induced systemic oxidative imbalance. Our data are in line with previously published data which indicated that wogonin exhibits strong antioxidant activity in several in vitro and in vivo models [33,34]. It was previously reported that wogonin protects against cadmium-triggered oxidative renal injury [52].…”
Section: Effect Of Wogonin On Serum Lipid Peroxidessupporting
confidence: 93%
“…[32]. Wogonin also has been reported to have a potential antioxidant activity [33,34]. Accordingly, the current study aimed at investigating the potential protective activity of wogonin against DEX-induced oxidative stress in vivo in Sprague Dawley rats.…”
mentioning
confidence: 99%
“…Surprisingly, these compounds are both flavonoids which have antioxidant and antiinflammatory effects [39][40][41][42]. For instance, researches indicated that quercetin mediate the anti-inflammatory mechanism of reducing acute laryngitis by restoring the Th17/Treg balance and activating heme oxygenase 1 and isorhamnetin increased the levels of TNF-α, IL-1β, IL-6, IL-17A, and IL-17F as well as decreased levels of IL-35 and IL-10 in the CIA mice, resulting in an anti-inflammatory effect [43,44]. Luteolin prevented cartilage destruction in OA rats in vivo through inhibiting IL-1β-induced phosphorylation of NF-κB [45].…”
Section: Discussionmentioning
confidence: 99%